Digital art technology and its reflection on the recipients (Journal of the College of Basic Education, 2022)
Technology has changed many concepts in human life at various levels, especially in the last century and the beginning of the current century, where it has become an important part in all aspects of life in general, art in particular, and plastic arts, one of these arts that have been affected by the technological revolution, so we live in virtual worlds through tablets and devices. Communications close together and coexist with each other, so that our lives turn into numbers and pictures. We interact and communicate within these virtual worlds. The picture was one of these things that the hand of technology touched to transform and change, so the tagged research (digital art and reflexive interaction), whose problem revolves around the ability of digital art to interact Its surroundings to be alternate work patterns and to find out how effective it is to be parallel, not hypothetical, where the researcher divided the research into two topics. The first dealt with image transformations and their societal work and the extent of technology's impact on the image and its construction in terms of color, points and shape, and how the panels turned into electronic goods that can be acquired and how to deal with them and feel about them. As for the second topic, it dealt with digital work and its relationship with the recipient, and how it can be done He has to deal with this art, so the recipient of digital creativity will find a new world in which there are technologies that correspond to other arts. Therefore, the task of digital criticism in research is the essence, minutes and characteristics of digital culture, as it becomes necessary for criticism to study issues of image predominance thanks to the employment of digital technology Through the objective and conscious approach to the secrets of technological techniques in analyzing the creative digital artwork and highlighting its initial elements that formed it, the researcher also touched upon the most important artists of this type of art with a review of the most important programs that she works on, while the third chapter included a group of paintings that the researcher analyzed in light of the indicators that As a result of the theoretical framework, which can build digital drawing and depends on a different set of electronic programs that specialize in design and drawing to build its shapes and paintings, which constitute art and form of postmodernism that has its own aesthetics that arouse the appetite and thought of the recipient connected to a set of results and conclusions that show the ability of And draw various models and paintings using various programs for drawing and repairing pictures with a calculator, or curling devices and devices. For another with controlling various details to produce various shapes and paintings with different artistic and aesthetic values. The research included the sources and references that the researcher used in writing her research .